Միջմշակութային և միջանձնային հաղորդակցության դերը օտար լեզու ուսուցանելիս - Գոհար Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматриваются различные аспекты роли межкультурной коммуникации. Определяются методы и подходы коммуникативного обучения иностранным языкам в современном образовании. The article comprises various aspects of the role of intercultural communication. Approaches of communicative foreign language teaching methods in modern educational system are discussed.
Keywords: Education; Language and Literature